Design, Validation and User Experience of the Faculty Development Interprofessional Education for Interprofessional Collaborative Practice (IPE-4-IPCP) Online Learning Modules - Bogossian, Fiona; Hepburn, Stevie-Jae; Dodd, Natalie; healy, Katie; New, Karen; Shakhovskoy, Rebekah; Pelly, Fiona; Williams, Jen; Taylor, Jane (International Journal of Practice-based Learning in Health and Social Care, 2025)
Faculty development is significant in facilitating interprofessional education (IPE), yet faculty often have limited training. This paper describes the design, validation and user experience of four Faculty Development Interprofessional Education for Interprofessional Collaborative Practice (IPE-4-IPCP) online learning modules. Multi-methods research conducted at a health institute in QLD, Australia in 2022. An expert panel (n=5) and health faculty (n=8) assessed content and face validity. User group experience was explored qualitatively via focus groups. Content validity indices were all >0.8 indicating that content was appropriate. Agreement on all scales exceeded 75% for face validation. Focus groups findings suggest that the four IPE-4-IPCP modules reinforced current faculty practices, taught new concepts, used language that was inclusive and, will assist faculty to implement IPE in their context. Carefully designed online learning modules can be an effective way to engage and support faculty involved in design, implementation, assessment and evaluation of IPE experiences.